Acúmulo de nutrientes e crescimento do pinhão manso no oeste do Paraná - Frandoloso, Jucenei Fernando (2013)
The objective of the study was to evaluate the growth, the gait of absorption and accumulation of nutrients and the crop yield of jatropha in the western region of Paraná. For production of seedlings we used seeds coming from Dourados - MS, planting a seed in each tub of 120 cm3 of substrate. The time of formation of the seedlings was 60 days after sowing. The field experiment was carried out in the period of December 2009 to December 2011, in spaced of 3 x 2 , in an Oxisol dystrophic anagen bulbs (O D A) at the experimental station of Pato Bragado PR, belonging to the core of experimental stations of the State University of Paraná, under the geographical coordinates 24 39 43 S e 54 15 53 W and altitude of 247 meters. During the experimental conduction the fertilization of coverage with 40 kg ha -1 of N and 40 kg ha -1 of K 2 O annually. The experimental design was a completely randomized design with four replicates, and it used a plant of each block every 90, 180, 270, 360, 450, 540, 630 and 72 days after transplanting (DAT) which after the measures that were not destroyed were cut close to the soil and separated in leafs, stems, petioles and flower and fruit, and put up for drying. The assessments of the growth of the plants consisted of the measure of the height of the plant, the stem diameter number of leafs, area of the cup, mass of dry leaves, petiole, branches and fruits, when present, determination of leaf area LA, rate of absolute and relative growth (RAG and RRG), reason of leaf area (RLA), reason weight of leaf (RWL), and leaf area index (LAI). For the chemical analysis of nutrients, representative samples of the different components of the plant were passed in mill type Willye and stored for future determination of mineral elements. For determination of the total quantity of nutrients accumulated in each part of the plant the concentration of each nutrient was multiplied by the mass of the dry material of the said component in each time of sampling. The monitoring of fruit production, was performed in additional area, in 32 selected plants. The analysis data of growth, of dry material, concentration and accumulation of nutrients in each component were submitted to statistical analysis using the program Sigmaplot12. The cultivation of jatropha presents linear growth in height and diameter of the base in the early years of cultivation. The jatropha curcas has a period of vegetative rest well defined, and it is in the months of March to September; the greatest mass of dry leaves, mass of petiole and the highest number of leaves occur in the month of December of each year along with the largest leaf area with increments of more than 100% in this parameter from one year to another, the absolute growth rate (and the leaf area index (LAI) exhibit higher values at the end of each year, the relative growth rate, ratio of leaf area and the reason weight of leaves have higher values at the beginning of each year; the production of jatropha shows values of 93 g per plant at 18 months of age, with harvest period in the months of January to July in the region. The total accumulation of macronutrients followed the following descending order K, Ca,N,Mg,P,S. The macronutrients P, K, and Mg present redistribution to the stem in the period of leaf senescence. In the fruits (seed + shell) the order of accumulation was N,K,Ca, P, Mg, S. The total accumulation of micronutrients obeyed the following order: Mn, Fe, Zn, B, Cu, Mo and in ripe fruits the order was: Fe, Mn, B, Zn, Cu, Mo. The micronutrients Cu, Zn and Fe present redistribution to the stem in the period of leaf senescence. The export of macronutrients by fruits is high, and is needed 199,69 and 306 kg ha-1, of N, P 2 O 5 and K 2 O, respectively for the production of 4000 g/plant in a population of 1667 plants ha-1. The recommendations for fertilization of coverage in the western region of Paraná must be carried out in the period from September to march, depending on the water regime it is suggested to use formulated with the relationship N:P 2 O 5 , K 2 O of 2,88:1,0:4,4.